Zakat on Business Entities and its Tax Treatment - Muhammad Ali Nuruddin; Muslich Anshori; Imron Mawardi (MediaTrend, 2023)
The focus of this paper is on zakat on business entities and its tax treatment, whether the zakat clause as a deduction from taxable income regulated in Law Number 23 of 2011 concerning zakat management and Law Number 36 of 2008 concerning the Fourth Amendment to Law Number 7 of 1983 concerning Income Tax affects taxable income and income tax that must be paid by the company. The research approach is a case study where the sampling business entities are companies engaged in property services whose income tax calculation is final and companies in the trading sector whose tax calculation uses the tariff of article 17 of the Income Tax Law. The results of the study provide legal certainty for business entities that pay zakat and become input for government policy in the management of zakat and taxation. If zakat payment is recognized as a deduction, it can encourage more active zakat payment and increase the contribution of zakat to state revenue. However, if zakat payment is not recognized, business entities may face higher tax burden which has implications on their financial planning. This research contributes to the understanding of zakat and taxation in Indonesia and has implications for the legal framework and tax regulations.